ECOLOGICAL COURT AS THE GUARANTEE OF PROTECTION OF RIGHTS OF HUMAN AND CITIZENS - J. A. Krasnova; M. A. Deineha; L. Yu. Honcharuk; L. O. Sviatchenko (Scientific Journal of Pedagogy and Economics, 2019)
The article presents the results of the legal analysis of the foreign experience in the formation of the ecological courts, as one of the guarantees of the protection of rights of human and citizens. It is established that on the current date in the whole world there is a large number of the different variants and forms in which the environmental justice is carried out. Each country has its own specifics, related to its legal system and the place that is given up in its legal protection of the environment. It is detected that there are three types of systems of ecological justice in the world, namely: 1) systems that transfer environmental affairs to the courts of the general jurisdiction; 2) systems based on the internal specialization of the judiciary (creation of green benches, so called «green shops» or green judges without formal change of the judicial structure); 3) systems in which innovative environmental courts or tribunals are created. The first type includes the judicial systems of the most countries of the Romano-Germanic law, as well as Ukraine. The second involves the US judicial system (Vermont and Hawaii), Austria, a number of countries in Asia and South America. The third type of environmental justice system is the most innovative and progressive, based on the practice of Sweden, Australia, New Zealand, India, etc. It is considered that the analyzed examples of introduction the ecological justice, as well as the tendencies for the continuous increase in the number of ecological courts in the world, shall demonstrate the efficiency and viability of the specialized environmental justice. In our opinion, the main advantages of such courts are the expertise of the judiciary, public engagement, and a broad field for the use of mediation. The introduction and establishment of the ecological courts in Ukraine is necessary, considering a number of problems that exist in the domestic environmental legislation and enforcement activities, as well as the progressive world trends. It should be gradual and include three functional stages: 1) preparation of judges who would be competent regarding the scope of their specification, which would begin their activity in courts of general jurisdiction, but their respective competence would include relevant environmental disputes; 2) creation of «Green benches». At this stage, it would be advisable to foresee, besides imposing the responsibility of ecological justice, also the obligation to allocate the resources; 3) creation of the system of the specialized ecological courts.